Coupling methane and bioactive polysaccharide recovery from wasted activated sludge: A sustainable strategy for sludge treatment. (15th April 2023) - Liu, Jie; Zhang, Zi; Deng, Yangfan; Sato, Yugo; Wu, Di; Chen, Guanghao
Highlights: The simultaneous recovery of CH4 and PSs from waste activated sludge was examined. PSs extraction before anaerobic digestion (AD) increased CH4 production by 30.7%. The effects of AD on PSs composition and bioactivities were evaluated. The correlations between the composition and bioactivities of PSs were determined. PSs recovery before AD was the best coupling strategy based on environmental impacts. Abstract: Bioactive polysaccharides (PSs) are valuable resources that can be extracted from waste activated sludge (WAS). The PS extraction process causes cell lysis that may enhance hydrolytic processes during anaerobic digestion (AD) and thus increase the methane production. Thus, coupling PSs and methane recovery from WAS could be an efficient and sustainable sludge treatment. In present study, we comprehensively evaluated this novel process from the efficiencies of different coupling strategies, properties of the extracted PSs, and environmental impacts. The results showed that when the PS extraction was before AD, it produced 76.03 ± 2.00 mL of methane per gram of volatile solids (VS) and afforded a PS yield of 6.3 ± 0.09% (w:w), with a PS sulfate content of 13.15% ± 0.06%. In contrast, when PS extraction was after AD, the methane production decreased to 58.14 ± 0.99 mL of methane per gram of VS and afforded a PS yield of 5.67% ± 0.18% (w:w) in VS, with a PS sulfate content of 2.60% ± 0.04%. When there were two PS extractions before and after AD, the methane production, PS yield and sulfate content were 76.03 ± 2.00 mL of methane per gram of VS, 11.54 ± 0.62% and 8.35 ± 0.12%, respectively. Then, the bioactivity of the extracted PSs was assessed by one anti-inflammation assay and three anti-oxidation assays, and statistical analysis revealed that these four bioactivities of PSs were influenced by their sulfate content, protein content and monosaccharide composition, especially the ratios of arabinose and rhamnose. Furthermore, the environmental impact analysis shows that S1 was the best in five environmental indicators compared with other three non-coupled processes. These findings suggest that the coupling PSs and methane recovery process should be further explored to determine its potential for large-scale sludge treatment. Graphical abstract: Image, graphical abstract